2013
DOI: 10.1155/2013/476271
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of Azo Dye from Wastewater Using Bimetal‐Chitosan

Abstract: We introduce a new adsorbent, bimetallic chitosan particle (BCP) that is successfully synthesized and applied to remove the orange II dye from wastewater. The effects of pH, BCP quantity, and contact time are initially verified on the basis of the percentage of orange II removed from the wastewater. Experimental data reveal that the Cu/Mg bimetal and chitosan have a synergistic effect on the adsorption process of the adsorbate, where the dye adsorption by Cu/Mg bimetal, chitosan alone, and bimetal-chitosan is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The first sharp portion (t 0.5 = 1.41 À7.07 min 0.5 ) can be act as the external mass transfer. The second subdued section is the slow adsorption stage, where intraparticle diffusion is rate-controlled [2,35]. However, it can be found that none of plots give linear straight line passing through the origin (C 6 ¼ 0) ( Table 4).…”
Section: Kinetic Behaviormentioning
confidence: 99%
“…The first sharp portion (t 0.5 = 1.41 À7.07 min 0.5 ) can be act as the external mass transfer. The second subdued section is the slow adsorption stage, where intraparticle diffusion is rate-controlled [2,35]. However, it can be found that none of plots give linear straight line passing through the origin (C 6 ¼ 0) ( Table 4).…”
Section: Kinetic Behaviormentioning
confidence: 99%
“…Azo dyes, a main class of synthetic dyes applied to colorize various products, are complex organic compounds that are toxic and environmentally-resistant (Asgari et al, 2013a). Indeed, the presence of the azo group(s) bound to aromatic rings make azo dyes a very complex and biorecalcitrant class of SOCs (Ramavandi and Farjadfard, 2013;Dong et al, 2007); therefore, they are suitable candidates for examining the catalytic activity of CMA-chitosan and its ability to degrade recalcitrant compounds in the catalytic oxidation process. This is the first instance of the use of a fishery-waste base supporting the CMA in order to remove OG from the wastewater through FBR.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Table 4, values of E were in the typical range of bonding energy for chemisorption (8 -16 kJ/ mol) (22), which demonstrated that in the adsorption of copper onto BSO, ion-exchange and chemisorption played a key role. This data reconfirmed the result obtained from the kinetic study.…”
Section: (6)mentioning
confidence: 78%
“…Based on the Langmuir constant, the value of R L for copper adsorption with BSO falls between 0 and 1, which affirmed that copper adsorption was favorable under the selected conditions of this study. In addition, it is known that 1/n in the Freundlich model is adsorption intensity and the values of 1/n indicate the type of isotherm to be irreversible (1/n = 0), favorable (0 < 1/n < 1), or unfavorable (1/n > 1) (22). As shown in Table 4, the 1/n of the Freundlich isotherm obtained was 0.448, which revealed that copper was favorably adsorbed onto BSO.…”
Section: (6)mentioning
confidence: 99%